Heritage, Space, and Satisfaction: Visitor’s Perceptions of the Businesses in the Old City of Lasem, Indonesia - Odilia Renaningtyas Manifesty (Departement of Architecture, Universitas Islam Indonesia, 2025)
Lasem, Central Java, reflects a rich blend of Javanese and Chinese heritage, offering both opportunities and challenges in cultural tourism and preservation. This study explores how online customer feedback reveals visitor perceptions of Lasem’s architectural and cultural elements, particularly in relation to Batik and Peranakan architecture. Using data from 13 Google Maps-reviewed businesses, the study employs quantitative and qualitative methods, analyzing star ratings, review lengths, keyword frequency, and thematic patterns. Findings show that visitor satisfaction is closely tied to cultural authenticity. Positive reviews often emphasize appreciation for heritage experiences and the adaptive reuse of historic buildings, while lower ratings highlight infrastructure issues such as water and room quality. The results underscore the role of vernacular spaces in shaping meaningful tourist experiences and highlight the need to balance heritage preservation with the expectations of modern visitors. This research offers insights for improving heritage site management and supporting sustainable cultural tourism in small historic towns.